2022
DOI: 10.1093/neuonc/noac088
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive profiling of myxopapillary ependymomas identifies a distinct molecular subtype with relapsing disease

Abstract: Background Myxopapillary ependymoma (MPE) is a heterogeneous disease regarding histopathology and outcome. The underlying molecular biology is poorly understood, and markers that reliably predict the patients’ clinical course are unknown. Methods We assembled a cohort of 185 tumors classified as MPE based on DNA methylation. Methylation patterns, copy number profiles, and MGMT promoter methylation were analyzed for all tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…MPEs constitute a distinct class of ependymoma, as shown by methylome analysis studies 2,3,40 . Witt et al studied 122 ependymal tumors, showing that all tumors morphologically diagnosed as MPEs clustered to the “ependymoma, myxopapillary” category.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…MPEs constitute a distinct class of ependymoma, as shown by methylome analysis studies 2,3,40 . Witt et al studied 122 ependymal tumors, showing that all tumors morphologically diagnosed as MPEs clustered to the “ependymoma, myxopapillary” category.…”
Section: Discussionmentioning
confidence: 98%
“…The possibility of two distinct types of MPE was further explored in a study of 185 MPEs, which demonstrated a subset of tumors in younger patients with predominantly papillary morphology, characterized by MGMT promoter hypermethylation, increased copy number alterations and aggressive clinical course. A second subset of tumors with significantly better clinical outcomes, despite their tanycytic morphology and greater cellular pleomorphism, was identified in older patients 40 . Data from next‐generation sequencing (NGS) studies are limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HOXB13 is highly expressed in the tail bud of the developing embryo; in adults, it is most highly expressed in the mature prostate, where it is implicated in tumor development, 12,13 and in distal colonic mucosa. It has been localized with strong staining in myxopapillary ependymomas 11,14 that are clearly unrelated tumors. While it has not been found in PGLs at other sites, its expression in other NETs remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal ependymomas are made up of SP-sub-ependymoma, SP myxopapillary ependymoma, and SP ependymoma. A recent study by Bockmayr et al demonstrated that SP myxopapillary ependymoma is molecularly comprised of two distinct subgroups, MPE-A and MPE-B; with the former being associated with significantly higher relapse rate and decreased progression-free survival [91].…”
Section: Ependymomamentioning
confidence: 99%